Corrigendum to “Synthesis of Kojic Ester Derivatives as Potential Antibacterial Agent” - Zainab, Binti Ngaini; Zie, Carolynne Wei Sie; Nurashikin, Binti Suhaili; Eswaran, Madiahlagan (Hindawi Publishing Corporation, 2019)
In the article titled “Synthesis of Kojic Ester Derivatives as Potential Antibacterial Agent [1],” the sentences “Acetophenone (1.2 g, 0.1 mmol) was added to 4-carboxybenzaldehyde derivatives (0.15 g, 0.1 mmol) in methanol (50 mL). KOH (1.7 g, 0.3 mmol) in methanol was added and the mixture was stirred at room temperature for 4 h under nitrogen atmosphere” in Section 2.2 should be changed to “Acetophenone derivatives (1.2 g, 0.1 mmol) were added to 4-carboxybenzaldehyde (0.15 g, 0.1 mmol) in methanol (50 mL). KOH (1.7 g, 0.3 mmol) in methanol was added, and the mixture was stirred at room temperature for 4 h under nitrogen atmosphere.”